An IMS architecture and algorithm proposal with QoS parameters for flexible convergent services with dynamic requirements (2010)
Quality of Service (QoS) provisioning is one of the main requirements in the 3GPP IP Multimedia Subsystem (IMS) and it has been addressed in different works since the beginning of the IMS standardization process. As a result of the fixed and mobile networks evolution, parameters standardized in IMS have changed constantly until the specification of the Policy and Charging Control (PCC) architecture that integrates IMS QoS and Charging functionalities. However, current IMS QoS specifications still have some limitations to handle service flexibility that is required to provide Internet services over IMS. In this work, we propose an enhanced IMS QoS architecture to support efficient QoS providing for flexible services with dynamic requirements. This proposal is compared against different approaches to evaluate their behavior under network saturation conditions. Simulations results show that the architecture we propose achieves efficiency and flexibility, maintaining the number of blocked and active sessions, and increasing the number of high priority sessions activated in a saturated network.